Interpersonal Communication Strategy and Cultural Adaptation in Sriwijaya Dormitory - Berliano, Ramadhan; Fajri, Choirul (Manunggal Halim Jaya, 2025)
This research investigates the strategic role of interpersonal communication in mitigating culture shock experienced by students living in the Balai Sriwijaya male dormitory in Yogyakarta. It specifically addresses the following research questions: (1) How do students employ interpersonal communication strategies to cope with cultural dissonance? Moreover, (2) In what ways does such communication facilitate their psychological and cultural adjustment? Employing a qualitative case study design, data were gathered through in-depth interviews and analyzed using thematic interpretation. The study reveals that interpersonal communication is not merely supportive but also transformative in enabling students to navigate cultural dissonance and psychological adaptation. Findings highlight three core mechanisms: first, relational openness that fosters emotional safety and reduces uncertainty; second, peer-driven empathetic support that functions as a coping framework against disorientation and homesickness; and third, active cultural negotiation through daily dialogue, allowing students to reconstruct a hybrid identity without rejecting their cultural roots. The dormitory context serves as a living laboratory for intranational intercultural exchange, where communication becomes the primary tool for fostering inclusion, emotional resilience, and cognitive adaptation. Rather than passive assimilation, students engage in reciprocal meaning-making processes that reshape their worldview and strengthen their cultural competence. This study contributes to the scholarship of interpersonal and intercultural communication by contextualizing cultural adaptation within a domestic, student-based microenvironment. The implications underscore the need for intentional communication spaces in educational housing to foster inclusive and adaptive communities amid cultural diversity.